Jump in the structure of Type I kerogen revealed from pyrolysis and 13C DP MAS NMR. (October 2017) - Gao, Yuan; Zou, Yan-Rong; Liang, Tian; Peng, Ping'an
Highlights: Five kerogen molecular models within the 'oil window' constructed. Jump in the structure of a Type I kerogen observed near peak oil window. Alkyl degradation and growth in aromatic cluster number contributed to aromaticity increase. Both aliphatic and aromatic structures generated hydrocarbons before peak oil window. Abstract: Artificial maturation of Maoming oil shale kerogen (Type I) was performed at a heating rate of 5 °C/h in a closed Au tube system. Yields of pyrolysis products (C1–5, C6–14, C14+ and insoluble residue) were quantified. The insoluble kerogen residue was analyzed using Rock-Eval, elemental analysis and quantitative 13 C direct polarization/magic angle spinning (DP MAS) nuclear magnetic resonance (NMR) spectroscopy. Peak oil generation was achieved at Easy %Ro 0.95. A "three-stage" relationship existed between aromaticity and Easy %Ro because of the relatively pronounced cleavage of aliphatic carbons and the formation of new aromatic structures in the kerogen residue. Five models of kerogen representing five stages in the oil window were drawn to provide a visualized kerogen structure modification with evolution. A novel jump in the structure of the kerogen residue was observed at ca. Easy %Ro 0.80–0.90, corresponding to the peak oil window. Our results suggest that aromatic carbon, replacing aliphatic carbon and becoming the dominant carbon in the residue, was the cause of the dramatic changes in the Easy %Ro interval of 0.80–0.90. Both aliphatic and aromatic structures contributed to hydrocarbon generation before peak oil generation. CH2 groups contributed most to the hydrocarbon generation potential. Me groups contributed little to hydrocarbon generation within the oil window.